Expression of vascular endothelial growth factor and microvessel density in psoriatic skin lesions - Priya T Rajan; T N Suresh; T S Rajashekar (Wolters Kluwer Medknow Publications, 2018)
Background: Psoriasis is a common chronic and immune-mediated skin disorder having a significant impact on the patient's quality of life. An analysis of the role of angiogenic vascular endothelial growth factor (VEGF) expression and microvessel density in psoriatic skin lesions may help in better understanding of the disease pathogenesis. The aim of this study was to examine the expression of vascular endothelial growth factor (VEGF) and microvessel density using CD34 antibodies in psoriatic skin lesions by immunohistochemical examination using normal skin of healthy individuals as controls. Materials and Methods: Patients with clinical diagnosis of plaque type of psoriasis (e.g., chronic plaque) (n = 49) were included in the study. 5-mm punch biopsies were taken from the psoriatic skin lesions in these patients. A total of 20 punch biopsies were taken from the control group comprising of 20 healthy volunteers. The biopsies were subjected to histopathological examination for confirmation of diagnosis and grading. Immunohistochemical evaluation was done for the expression of VEGF, and microvessel density was assessed using CD34 and compared with the controls. Results: An increased VEGF expression by keratinocytes (49.80% ± 21.16%) and microvessel density in the papillary dermis (15.302% ± 3.8061%) was observed in patients with psoriasis, which was significantly higher as compared to controls (P < 0.0001). A significant positive correlation was observed between VEGF expression by keratinocytes and the microvessel density in the dermis (r = 0.664, P = 0.01). No significant correlation was observedbetween the histopathological grade of psoriasis and microvessel density, or with the VEGF expression. Conclusion: VEGF expression ascertained to be a significant factor in the pathogenesis of psoriasis.